Використання молекулярних маркерів на основі генів відповіді на стрес для аналізу генетичного різноманіття Gentiana lutea L - Мосула, М.З.; Мельник, В.М.; Конвалюк, І.І.; Каспрук, Н.Г.; Дробик, Н.М.; Кунах, В.А. (Фактори експериментальної еволюції організмів, 2015)
The aims of the work was to determine the level of genetic diversity of G. lutea populations from two mountain ranges
(Chornogora, Svydovets) of Ukrainian Carpathians. Methods. Genetic variability of 86 plants from six populations was
assessed using CDDP fingerprinting with 6 primers. To evaluate the genetic polymorphism, the percentage of polymorphic
loci (P), Shannon’s information index (S), expected heterozygosity (He), gene flow (Nm), Jaccard’s (Dj
) and Nei’s (DN)
genetic distances were calculated. Results. Using CDDP primers, 120 bands were generated, and 95.8 % of those were
polymorphic. The relatively high level of genetic diversity was revealed in G. lutea populations (P = 31 %, S = 0.167,
He = 0.112). According to the Bayesian analysis, the populations were clustered in six different groups. Analysis of
molecular variance (AMOVA) showed that the differences between populations account for 71 % of total genetic variation,
whereas only 29 % of it were resided within populations. Agropopulation from Pozhyzhevska Mountain had low values of
genetic polymorphism (He = 0.056, S = 0,089, P = 18.3 %, Dj
= 10.9 %). Conclusions. The obtained results of AMOVA
indicate significant genetic isolation and differentiation of G. lutea populations. Comparison of G. lutea populations from
Chornogora and Svydovets ranges showed that the former have a higher level of genetic heterogeneity. The low level of
genetic diversity of Svydovets populations makes it necessary to protect them to ensure their survival.
Keywords: Gentiana lutea L., genetic polymorphism, CDDP-PCR, differentiation of populations.